Intermedial Aspects of Ukrainian Literature in the Age of the Sixties: Aesthetics Against Ideology - Савчук, Григорій Олегович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article contains an analysis of the intermedial component of creativity L. Kostenko, V. Symonenko, I. Svetlychny. The example of the poems "Van Gogh", "Ukrainian melody", "Pagan Spring" shows the function of pictorial, musical and cinematic elements in the construction of lyrical works, which are embodied in the context of Ukrainian literature of the sixties. It is shown that in the poem "Van Gogh" the question of freedom of creativity is disclosed in the widest context, a freedom that borders on insanity. In the poem "Ukrainian melody" the Ukrainian instruments – military drums and bandura – were opposed, it was possible to conclude that the poet chooses in favor of the drums that call on the battle. Symbolically, the drums are a poetic word that becomes a weapon. In the poetry "Pagan Spring", intermediate elements are associated with the theme of the renewal, the freedom that the spring has. It is proved that these intermedial complexes increase the weight of the aesthetic criterion. It is concluded that intermedial aesthetics can withstand the Soviet ideology.